Defining the Lead Isotopic Fingerprint of Copper Ores from North‐West Spain: The El Milagro Mine (Asturias). (13th December 2012) - Huelga‐Suarez, G.; Moldovan, M.; Suárez Fernández, M.; Ángel De Blas Cortina, M.; Ignacio García Alonso, J.
<x xml:space="preserve">Abstract</x> This study is focused on the El Milagro mine (Asturias, Spain) and is part of a large‐scale effort on the measurement of the lead isotopic composition of Spanish copper ores from prehistoric mines in the provinces of Asturias and León, from which no data were available until recently. Lead isotopic values are compared to the published lead data from the El Aramo mine in the same region. The results show that both mines have a very similar lead isotopic composition, apart from some highly radiogenic samples in the El Milagro mine, which are clearly different from those previously reported for the Iberian Peninsula.